The Grab Bag Book : Your Ultimate Guide to Liferaft Survival. - Howorth, Frances (Bloomsbury Publishing, 2013)
The purpose of this text is to ensure the survival of skipper and crew in the event of their boat sinking. It features: advice on the essentials to pack into the emergency grab bag for a short or long cruise, hot or cold climate, coastal or offshore trip; flowcharts to prioritise abandon ship procedure; techniques for survival in the liferaft, short- and long-term - the why, when and how of liferaft survival; and checklists and tables.